FILSAFAT PENDIDIKAN PRAGMATISME Telaah Atas Teori Manajemen Pendidikan John Dewey - Ahmad Kosasih (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2022)
Philosophy in educational management provides a philosophical basis for how the real management of education is built on the basis of a strong scientific perspective. A philosophical basis is needed in educational management or educational science experts in order to develop their knowledge productively and responsibly. The analysis is needed to explain how the ontological, epistemological and axiological workings of the science are developed. In this study, John Dewey's philosophy of pragmatism can at least provide theoretical reinforcement to the pragmatism-based philosophy of management education that he developed. Dewey's pragmatism philosophy can at least provide a theoretical foundation for how to understand the context of education, which has to do with the human process in finding answers to life based on their experiences. That, in the process of discovery, efforts to understand the close relationship between action and thought, between experiment and reflection are based on scientific principles. From here, the criteria for academic truth through education are seen as having uses for real human life.